Pengaruh Citra Merek dan Kepercayaan Merek Terhadap Keputusan Pembelian pada Marketplace Shopee di Wilayah Kota Surabaya - Pudyardana, Waode Monica; Aribowo, Handy (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to understand how brand image and brand trust influence purchasing decisions at the Shopee marketplace in the Surabaya city area. This study uses an associative quantitative research method, in which the authors conducted a survey by distributing questionnaires to Shopee users in Surabaya. Then, the validity and reliability of the data were assessed and analyzed using multiple linear regression methods. The number of samples in this study were 120 users, who were selected using accidental techniques. The results showed that brand image has a significant positive influence on purchasing decisions, with the t-test results showing a significance level of 0.040, which is smaller than the 0.05 significance level set. In addition, brand trust also has a significant influence on purchasing decisions, with the t test results showing a significance level of 0.000. Overall, all the variables studied have a positive and significant effect on purchasing decisions, with the F test results showing a significance level of 0.000.